To transform the function \( f(x) = 3x \) into \( -f(3x-2) + 1 \), we will follow the steps required to manipulate the expression step by step.
Let's analyze how to perform the transformations:
- Start with \( f(x) = 3x \).
- Substitute \( 3x-2 \) into the function: \( f(3x-2) = 3(3x-2) \).
- Evaluate that expression: \( 3(3x-2) = 9x - 6 \).
- Apply the negative sign: \( -f(3x-2) = -(9x - 6) = -9x + 6 \).
- Finally, add 1 to the result: \( -9x + 6 + 1 = -9x + 7 \).
Now, we can fill out the table:
Transformation Steps Table
| Step | Expression | Value for \( x \) | |------|-------------------------------------------------|-------------------| | 1 | \( f(x) = 3x \) | | | 2 | \( f(3x - 2) = 3(3x-2) \) | | | 3 | \( 3(3x - 2) = 9x - 6 \) | | | 4 | \( -f(3x - 2) = -(9x - 6) = -9x + 6 \) | | | 5 | \( -9x + 6 + 1 = -9x + 7 \) | |
Next, let’s input a particular value for \( x \) to evaluate the function at different steps:
Let's say we evaluate \( x = 1 \):
- For \( f(1) \), we calculate \( f(1) = 3(1) = 3 \).
- Substitute \( x = 1 \): Compute \( f(3(1)-2) = f(3-2) = f(1) = 3 \).
- At that point, \( 3(1-2) = 3(1) - 6 = 9 - 6 = 3 \).
- Calculate \( -f(1) = -3 \).
- Finally: \( -3 + 1 = -2 \).
Inputting the calculated values based on \( x = 1 \):
- Row 1: \( 3 \)
- Row 2: \( 3 \)
- Row 3: \( 3 \)
- Row 4: \( -3 \)
- Row 5: \( -2 \)
Final Values
| x | In the order of operations, what would you do first? | |----|--------------------------------------------| | 1 | \( 3(1) = 3 \) | | 2 | \( 3(3(1) - 2) = 3(1) = 3 \) | | 3 | \( 3(3(1) - 6) = 3(9 - 6) = 3 \) | | 4 | \( -3 \) | | 5 | \( -3 + 1 = -2 \) |
Feel free to change \( x \) to any desired value to get different evaluations!